Generalised Henstock - Kurzweil Integral with Multiple Point (Baghdad Science Journal, 2023)
This paper deals with a new Henstock-Kurzweil integral in Banach Space with Bilinear triple n-tuple and integrator function Ψ which depends on multiple points in partition. Finally, exhibit standard results of Generalized Henstock - Kurzweil integral in the theory of integration.